2001
DOI: 10.1542/peds.108.5.e88
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental and Genetic Factors on Behavior Problems and Autistic Symptoms in Boys and Girls With Fragile X Syndrome

Abstract: ABSTRACT. Objective. Fragile X syndrome, caused by mutations in a single gene of the X chromosome (FMR1), is associated with neurobehavioral characteristics including social deficits with peers, social withdrawal, gaze aversion, inattention, hyperactivity, anxiety, depression, and autistic behavior. However, there is considerable variability in the behavioral and psychiatric problems among children with this condition. The purpose of this study was to measure genetic and environmental factors influencing behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
141
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 31 publications
9
141
0
2
Order By: Relevance
“…Our behavioral data are thus consistent with the observations by Reiss and coworkers (58,59), indicating that environmental factors positively influence the behavioral outcome in children with FXS. Although further investigations are needed to elucidate the molecular mechanisms involved in the enrichment effects, our findings demonstrate that some mechanisms of neuronal plasticity are preserved in FMR1-KO mice and can be triggered by environmental stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Our behavioral data are thus consistent with the observations by Reiss and coworkers (58,59), indicating that environmental factors positively influence the behavioral outcome in children with FXS. Although further investigations are needed to elucidate the molecular mechanisms involved in the enrichment effects, our findings demonstrate that some mechanisms of neuronal plasticity are preserved in FMR1-KO mice and can be triggered by environmental stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…In a longitudinal study of Ferdinand et al (2001), thought problems in childhood were associated with substance abuse (alcohol and tobacco) in young adulthood. Other studies showed TP in children to be associated with disorders, such as obsessive-compulsive disorder (OCD; Geller et al, 2004), multiple complex developmental disorder (MCDD;de Bruin et al, 2006) and fragile X syndrome (Hessel et al, 2006). The TP-syndrome also predicted DSM-III-R diagnoses of simple phobia, social phobia, separation anxiety disorder, mood disorders and psychotic disorders (Kasius et al, 1997).…”
mentioning
confidence: 99%
“…The gender of the individual with FRAX impacts significantly upon the expression of this syndrome due to the fact that FRAX is caused by a mutation on the X chromosome (Hessl et al, 2001). Females are protected from FRAX to some degree due to the presence of one unaffected X chromosome (Hessl et al, 2001).…”
mentioning
confidence: 99%
“…The gender of the individual with FRAX impacts significantly upon the expression of this syndrome due to the fact that FRAX is caused by a mutation on the X chromosome (Hessl et al, 2001). Females are protected from FRAX to some degree due to the presence of one unaffected X chromosome (Hessl et al, 2001). As a result, intellectual functioning in such females may not be impaired, with ID typically ranging from mild ID to no significant impairment (Bennetto & Pennington, 1996;Hagerman & Sobesky, 1989).…”
mentioning
confidence: 99%